The Photoperiod: Handling and Causing Stress in Plants - Roeber, Venja M.; Schmülling, Thomas; Cortleven, Anne (Frontiers in Plant Science, 2022)
The photoperiod, which is the length of the light period in the diurnal cycle of 24 hours, is an important environmental signal. Plants have evolved sensitive mechanisms to measure the length of the photoperiod. Photoperiod sensing enables plants to synchronize developmental processes, such as the onset of flowering, with a specific time of the year, and enables them to alleviate the impact of environmental stresses occurring at the same time every year. During the last years, the importance of the photoperiod for plant responses to abiotic and biotic stresses has received increasing attention. In this review, we summarize the current knowledge on the signalling pathways involved in the photoperiod-dependent regulation of responses to abiotic (freezing, drought, osmotic stress) and biotic stresses. A central role of GIGANTEA, which is a key player in the regulation of photoperiod-dependent flowering, in stress responses is highlighted. Special attention is paid to the role of the photoperiod in regulating the redox state of plants. Furthermore, an update on photoperiod stress, which is caused by sudden alterations in the photoperiod, is given. Finally, we will review and discuss the possible use of photoperiod-induced stress as a sustainable resource to enhance plant resistance to biotic stress in horticulture.